A intersetorialidade na política de enfrentamento à violência contra as mulheres em Minas Gerais - Pimenta, Beatriz Freire (2024)
This dissertation aimed to analyze intersectionality in the policy to combat violence against women in the state of Minas Gerais. Violence against women is a problem that affects countless women around the world and is something that needs to be on the public agenda of governments, since action through public policies is capable of protecting these women from the various types of violence they suffer every day. In this context, this work was constructed following an understanding that the problem of violence against women requires comprehensive actions on the part of public authorities, since it is considered a complex and multi-causal problem. In this sense, public policies designed to resolve this problem must be intersectoral and transversal. This argument is supported throughout the work through guidelines from the National Plans to Combat Violence Against Women, Federal Laws and International Conventions, which are shown throughout the research. So that the policy could be analyzed from the perspective of transversality, it was decided to use the analysis model developed by the organization Kaleidos.red (2010), which proposes an analysis in 3 dimensions of transversality: shaping factors, tangible factors and intangible factors. This work mapped and described which actors act on the agenda in the state, as well as describing the actions carried out by these actors in relation to combating violence against women in Minas Gerais in the period from 2019 to 2023. Given this context, these actions found support the policy to combat violence against women in Minas Gerais, which was analyzed using the categories established by Kaleidos.red (2010). At the end of the research, it is concluded that although there are many actions being carried out in the state, the agenda still lacks institutionalization that would enable its continuity throughout the administrations, directly influencing its strengthening as a public agenda in the state.